2018
DOI: 10.1159/000494532
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Kleefstra Syndrome: Report of Two Novel Cases with Previously Unreported Features and Literature Review

Abstract: Kleefstra syndrome (KS) is a rare genetic condition resulting from either 9q34.3 microdeletions or mutations in the EHMT1 gene located in the same genomic region. To date, approximately 100 patients have been reported, thereby allowing the core phenotype of KS to be defined as developmental delay/intellectual disability, generalized hypotonia, neuropsychiatric anomalies, and a distinctive facial appearance. Here, to further expand the knowledge on genotype and phenotype of this condition, we report 2 novel cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 20 publications
(58 reference statements)
1
27
0
Order By: Relevance
“…Kleefstra syndrome is caused by the either a deletion or a mutation of the EHMT1 gene. Approximately 20% to 30% of patients have hearing loss . Ayyash et al and Tug et al reported Kleefstra syndrome in patients aged 5 and 12 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kleefstra syndrome is caused by the either a deletion or a mutation of the EHMT1 gene. Approximately 20% to 30% of patients have hearing loss . Ayyash et al and Tug et al reported Kleefstra syndrome in patients aged 5 and 12 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Kleefstra syndrome is caused by a subtelomeric chromosomal abnormality resulting in either a heterozygous microdeletion in chromosomal region 9q34.3 or by a mutation in the euchromatin histone methyltransferase1 ( EHMT1 ) gene . It is inherited in an autosomal‐dominant manner, but almost all reported cases have occurred de novo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As more and more studies on the neurological aspects of the MDEM emerge, reports on other brain malformations are revealed. Searching the literature for OB hypoplasia/aplasia in these conditions unveiled a large number of studies involving CHARGE syndrome (Lin et al, 1990;Harvey et al, 1991;Pinto et al, 2005), but only a couple of human reports on RSTS and KLFS (Ajmone et al, 2018;Ciaccio et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, previously reported cases were associated with other structural chromosomal abnormalities in addition to the deletion [45][46][47] . The DNA analysis was considered depending on ultrasound assessment result in prenatal cases [45][46][47][48][49][50] or visible clinical characteristics in postnatal cases [51][52][53][54] .…”
Section: Congenital Heart Malformationsmentioning
confidence: 99%